Towards a Pedagogical Model Applying Commedia dell'Arte and Art Workshops in Higher Education Design Studies - Haapaniemi Heini; Leinonen Teemu (De Gruyter, 2023)
This study introduces a pedagogical model: "the parallel co-inquiry cycles with performative inquiry for character related design" for higher education design studies that focus on characterization. The disciplines benefitting from cross-fertilization provided by the model include game design, fashion design, graphic design, theatre, and actor's art. Besides the model, the article discusses curriculum integration of a shared thematic denominator Commedia dell'Arte in higher education design studies. The model synthesizes progressive inquiry, drama pedagogical methodologies, and theories on theater with hands-on art workshops to create tangible and digital knowledge vessels for characterization. The research design relies on parallel co-inquiry cycles, participatory ethnography with elements from participatory design tradition. The model identifies three major components within the single 3E-inquiry cycles, namely exercise, experiment and experience. The entire process acquires complexity as each single inquiry cycle enters the next loop of Observe-Plan-Act-Reflect and more time and resources are allocated to the process. The pattern of action and reflection has an iterative cycle format in this model. Reflection has two distinguished purposes: first, to internalize reflective design and to become a reflective practitioner. Second, to see the importance of reflection as distancing oneself from the current process, to allow a reflective mind to linger on the process and learn from mistakes to turn them into assets. Reflection as a metacognitive skill has an all-encompassing purpose in both design and learning processes. The model distinguishes two types of knowledge vessels. Knowledge objects are abstractions that condense knowledge in the co-design process, whereas knowledge artifacts are concrete items, such as masks, outfits, and accessories in both digital and tangible formats. The model connects maker-culture, practice-based inquiry, and performative inquiry in the inquiry cycles. The drama method with performative inquiry acknowledges shared knowledge building in a collaborative, dialogical inquiry that fosters both argumentative and reflection skills.